Book Review: Data-Driven Innovation in the Creative Industries (Melissa Terras, Vikki Jones, Nicola Osborne and Chris Speed: Routledge, 2024). - Costelloe, Lucy (Irish Journal of Arts Management and Cultural Policy, 2025)
In Data-Driven Innovation in the Creative Industries, Melissa Terras, Vikki Jones, Nicola Osborne, and Chris Speed arrange a series of contributions across eleven chapters and additional case study segments that offer a new perspective on the topic of data-driven innovation for arts management, cultural policy scholars and arts practitioners alike. The book supports the objectives of not only clearly defining data-driven innovation but also stimulating conversations across a series of main themes from partnerships in digital technology, skills, frameworks and policy considerations. The eleven chapters are informed by the Creative Informatics initiative which showcases research conducted over five years in Edinburgh. The book explores the scope of data-driven innovation in the Creative and Cultural Industries and contributes significantly to the field of arts management and cultural policy but also opens up further avenues of research within other fields through the positioning of arts and cultural entities as both novel and interesting sites of study on innovation.